2007
DOI: 10.1017/s0266467406003877
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the population dynamics of the palm Sabal yapa in a landscape shaped by shifting cultivation in the Yucatan Peninsula, Mexico

Abstract: To understand the population dynamics of a species, it is necessary to document the way in which its demographic behaviour varies through space and time. Anthropogenic disturbance, such as shifting cultivation, is an important factor causing demographic variation in many tropical non-timber forest products. The leaves of the palm Sabal yapa are an important non-timber forest product used for thatching by Mayan peoples. The demography of Sabal yapa was studied in three habitats (mature forest, successional fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 49 publications
(50 reference statements)
0
21
1
1
Order By: Relevance
“…positive or negative contributions, respectively) in the λ value, compared to a reference average matrix. The contribution matrices for each site were calculated as follows (Pulido et al 2007):…”
Section: D) Retrospective Analysis: Life-table Response Experiments (mentioning
confidence: 99%
“…positive or negative contributions, respectively) in the λ value, compared to a reference average matrix. The contribution matrices for each site were calculated as follows (Pulido et al 2007):…”
Section: D) Retrospective Analysis: Life-table Response Experiments (mentioning
confidence: 99%
“…Ecological studies generally view the agricultural matrix as homogeneous and as a source of contamination of embedded forest patches (Janzen 1983, rather than viewing forest remnants as heterogeneous biodiversity sources and sinks within the broader landscape. By zooming out on the landscape matrix itself, we can investigate population dynamics and species interactions among component habitat types (agriculture, secondary vegetation, forest fragments) in a metapopulation or metacommunity context (Daily et al 2001, Vandermeer & Carvajal 2001, Perfecto & Vandermeer 2002, Bennett et al 2006, Kupfer et al 2006, Pulido et al 2007. Forest fragments and isolated remnant trees provide sources of propagules for re-populating surrounding areas and serve as resources, stepping stones, and refugia for wildlife that use multiple habitats (Bengtsson et al 2003, Guevara et al 2005.…”
Section: An Integrated Approach To Research In Human-modified Landscapesmentioning
confidence: 99%
“…We know virtually nothing about the long-term dynamics of populations and their genetic structure and variation within human-modified landscapes (but see Boshier et al 2004), as most studies of plant and animal diversity within agricultural landscapes have focused solely on describing static patterns of abundance and species richness. How are population processes affected by different land-use practices, landscape configurations, and levels of landscape modification and degradation (Cascante et al 2002, Boshier et al 2004, Komar 2006, Pulido et al 2007). The minimum amount of habitat needed to sustain species' population dynamics in a predictable time frame is defined as landscape threshold (Reunanen et al 2004).…”
Section: Population Biology and Long-term Monitoring Within Human Modmentioning
confidence: 99%
“…Their high overall use value and low availability might create high pressure on them, and these species should therefore be a priority in management plans. In these cases, their long-term maintenance would require the development of strategies of sustainable harvest based on traditional management techniques and studies of population ecology such as those developed by Olmsted and Álvarez-Buylla (1995), Martínez-Ballesté et al (2005), López-Hoffman et al (2006, Pulido et al (2007), and González-Insuasti and Caballero (2007). These studies have demonstrated the utility of defining harvest rates that allow maintenance of population growth, identifying cohorts of the populations to be protected and guiding practices directed at population recovery.…”
Section: Significance Of Plant Speciesmentioning
confidence: 99%